Use the quadratic formula to solve the equation. 2×2−6x+1=0 Enter your answers, in simplified radical form, in the boxes. Question Use the quadratic formula to solve the equation. 2×2−6x+1=0 Enter your answers, in simplified radical form, in the boxes. in progress 0 Math Bella 2 weeks 2021-10-11T19:18:23+00:00 2021-10-11T19:18:23+00:00 2 Answers 0

## Answers ( )

X= -b +- square root of b^2-4ac

——————-

2a

6 +- square root of 36-4(2)(1)

———

4

6+- square root of 32

———

4

6+- 4 square root of 2

———

4

3 +- 2 square root of 2

———

2

Answer with Step-by-step explanation:We have to solve the equation 2x²-6x+1=0

the solution of the equation ax²+bx+c=0 is given by

Here a=2,b=-6 and c=1

Hence, solution of 2x²-6x+1=0 is: